2006
DOI: 10.1002/aic.10834
|View full text |Cite
|
Sign up to set email alerts
|

Particle migration in the rotating flow between co‐axial disks

Abstract: We experimentally examine a dilute suspension of non-neutrally buoyant spherical particles migrating in a simple mixing tank at small but finite Reynolds numbers. We observe that the particles spontaneously migrate to repeatable non-trivial asymptotic locations within toroidal structures, located above and below at-disk impellers. The asymptotic migration positions include both the exact center of the torus and intermediate higher-order cluster locations within the flow whose stability is dependent on flow and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…We described separately the motion of particles in the invariant and mixing regions of the flow in terms of different values of the non-dimensional particle diameters and Froude numbers, which can also be expressed collectively in terms of a non-dimensional settling velocity, to account for the effects of inertia and gravity, respectively. We have shown using Poincaré maps that for the range of studied parameters, the uniform flow field inside invariant regions constitute strong barriers to transport, trapping heavy particles for long periods of time as has been observed in previous theoretical (McLaughlin 1988) and experimental investigations (Wereley et al 2002;Abatan et al 2006). Larger particle diameters, and in consequence larger Stokes numbers, set the conditions to increase stirring rates in these regions by allowing particles to escape.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…We described separately the motion of particles in the invariant and mixing regions of the flow in terms of different values of the non-dimensional particle diameters and Froude numbers, which can also be expressed collectively in terms of a non-dimensional settling velocity, to account for the effects of inertia and gravity, respectively. We have shown using Poincaré maps that for the range of studied parameters, the uniform flow field inside invariant regions constitute strong barriers to transport, trapping heavy particles for long periods of time as has been observed in previous theoretical (McLaughlin 1988) and experimental investigations (Wereley et al 2002;Abatan et al 2006). Larger particle diameters, and in consequence larger Stokes numbers, set the conditions to increase stirring rates in these regions by allowing particles to escape.…”
Section: Discussionsupporting
confidence: 60%
“…The efficiency of these filters is directly related to the capacity of the Taylor vortices and the azimuthal velocity gradient to capture and trap inertial particles. The fact that trapping zones coincide with invariant regions of the fluid flow has also been observed in the experiments of Abatan, McCarthy & Vargas (2006) for the flow in a cylindrical tank with co-rotating flat-disk impellers. Abatan et al (2006) showed that particles are displaced inside the toroidal regions after long periods of time, reaching different equilibrium positions either inward or outward towards the torus surface.…”
Section: Particle Trapping In Invariant Regionssupporting
confidence: 62%
“…Baffled tanks cause dead zones, actually worsening the mixing performance of an aeration system [1]. For the food and pharmaceutical industries it is a matter of primary importance to keep the reactor, as clean as possible; in crystallization processes [10] and biological applications [11] shear and impact are to be minimized; in precipitation processes baffles may suffer from incrustation problems [12]. Scientific literature shows an increasing interest in experimental investigations towards unbaffled stirred vessels [13][14][15][16][17][18][19][20][21][22][23][24][25] showing better potential for some industrial use of such type of stirred reactors.…”
Section: Introductionmentioning
confidence: 99%